"TROJEN HORSE" WHICH IS EMINENT WORK IN GREEK LITERATURE - Abdurahmonova N.B (TADQIQOTLAR.UZ, 2023)
ABSTRACT:The purpose of writing this article is give novices directly facts and information according to one of the eminent work with is" Trojen Hourse".In this article reader can find easily information related to this poem.For instance,What is the meaning of the "Trojen horse"? Why is poem much more popular? It is incredible how many proverbs and other elements of popular society from the past have been borrowed into the present day. Go online and go through Some Great Greek Myths for a fun read today! Which ones are your top picks? How come? Are there any proverbs or allusions to contemporary mainstream culture that originated with an ancient Greek myth? Would a modern Trojan horse function?